Physiological mechanisms of rapid and long-term thermal acclimation in a fish - Metz, Moa; Cowan, Zara-Louise; Leeuwis, Robine H.J.; Yap, Kang Nian; Lindgren, Mikael; Jutfelt, Fredrik (Pergamon Press, 2025)
To better cope with changing water temperatures, most aquatic ectotherms undergo physiological acclimation which often alters their thermal tolerance. The timeframe and relative contribution of various underlying mechanisms remain unclear, but are crucial to understand for predictions of climate change impacts. We investigated three candidate mechanisms involved in thermal acclimation in fish: heat shock protein expression (specifically HSP70), mitochondrial density (citrate synthase [CS] expression), and membrane fluidity (via spectroscopic fluorescence polarization). Zebrafish were acclimated to cold (20 °C), control (28 °C), or warm (35 °C) temperatures for two weeks, followed by half of each group receiving a 3-h heat shock to observe their potential for additional rapid acclimation (heat hardening). As expected, acute warming tolerance (CTmax) increased with long-term acclimation temperature. CTmax also increased by ∼0.5–1 °C following the 3-h heat shock, which is surprisingly fast. Expression of HSP70 in the brain was strongly upregulated after both long-term and rapid warm acclimation, aligning with the CTmax results. CS expression was not affected by thermal acclimation at these time scales. Membrane fluidity in muscle decreased for long-term warm-acclimated fish when measured at a common temperature (21 °C), whereas the 3 h heat shock had no effect. Collectively, this suggest that adjustments in membrane fluidity are slow while the heat shock response with HSP expression can act sufficiently fast to respond to rapid temperature fluctuations and is likely involved in determining thermal tolerance in fish.
Keywords: membrane fluidity; citrate synthase; teleost; CTmax; mechanisms; heat shock proteins